2015
DOI: 10.3354/meps11382
|View full text |Cite
|
Sign up to set email alerts
|

Coral reef species assemblages are associated with ambient soundscapes

Abstract: 12Coral reefs provide a wide array of ecosystem services and harbor some of the highest levels of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 49 publications
1
105
0
Order By: Relevance
“…Studies in other regions (Piercy et al 2014, Kaplan et al 2015 have also observed a positive correlation between spectral levels in this band and indicators of ecosystem function. It is intuitive to surmise that greater numbers of acoustically active organisms would create louder biological soundscapes.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Studies in other regions (Piercy et al 2014, Kaplan et al 2015 have also observed a positive correlation between spectral levels in this band and indicators of ecosystem function. It is intuitive to surmise that greater numbers of acoustically active organisms would create louder biological soundscapes.…”
Section: Discussionmentioning
confidence: 71%
“…Nondestructively determining whether there is any such relationship may be challenging as snapping shrimp are usually subterranean creatures and are rarely observed above the substrate. Directional acoustic re ceivers may be employed to determine the location of snaps in an area (Ferguson & Cleary 2001, Chitre et al 2012, Kaplan et al 2015, producing estimates of snapping shrimp distribution in a localized area. Re gardless of the process that connects high-frequency sound and the proportion of algal cover, the correlative findings shown here introduce the possibility of an acoustic indicator of algal dominance, and in some situations, of reef degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Wave energy and tidal or other currents are always minimal throughout the area. Biotic sounds experience small peaks around dawn and dusk but are uniform at other times [11]. These uniform water characteristics are not believed to be a major source of spatial or temporal variability on transmitter detections [4,6,12,13].…”
Section: Study Areamentioning
confidence: 99%
“…We will assess biodiversity diversity following new measurements developed for coral reef soundscapes, such as the median difference in daily max and min values (Kaplan et al 2015) and a fish-sound detector/classifier (Kaplan et al 2014). These measures seek to statistically quantify soundscape variability relative to the presence of OSW and changes in overall biodiversity between experimental and control areas.…”
Section: Monitoring and Assessment With Acoustic Techniquesmentioning
confidence: 99%